Moderation At Islamic University in Riau Province: a reviewed case - Miftahuddin Miftahuddin; Azni Azni; Akhmad Mujahidin; Khairil Anwar; Abu Anwar (AL-ISHLAH: Jurnal Pendidikan, 2022)
Multicultural society cannot always co-exist as they should. The challenge of a society that has a diversity of cultures, religions, languages and races at certain times becomes a serious problem for a nation. This is a struggle which is continuously encouraged by all elite figures. Likewise, it becomes a homework for academic people as the main actor to anticipate movements and thoughts that are counterproductive to the Islamic philosophy of moderation. This study is to detect and to serve as a benchmark for ideally a student in higher education as a relay for future Indonesian leaders. As many as 1051 students of  as respondents using quantitative descriptive survey methods. The instrument has been used to measure Islamic moderation with a fairly high level of reliability and validity. The results of this study found generally had a fairly good level of religious moderation and moderation in Islam. Even so, there are still a few who still have a direction of thinking that is counterproductive to Islamic moderation. Therefore this research is  important for assessment and development towards the formation of a way of thinking that has the characteristics of Islamic moderation, ummatan wasathan.